Post-annealing effects on excitonic states and defects in nanostructured Ti-doped ZnO thin films. (24th April 2019) - Darma, Y; Nurfani, E; Purbayanto, M A K; Widita, R; Rusydi, A; Takase, K
Abstract: We study the effects of post-annealing treatments on excitonic states and defects of nanostructured Ti-doped ZnO thin films grown by room-temperature magnetron sputtering technique. Here, the as-grown samples were annealed by varying the annealing environment, time, and temperature. We found that the higher excitonic emission was at 600 °C under N2 environment for 30 min. The excitonic states are analyzed by using spectroscopic ellipsometry, photoluminescence, and ultraviolet-visible absorption spectroscopy. Through critical point analysis of the complex dielectric function from spectroscopic ellipsometry, the energy of exciton is redshifted from 3.49 eV to 3.36 eV and the increase of excitonic transition is observed upon the annealing treatment. The weak excitonic transition in the as-grown sample is mainly due to the oxygen vacancies that promote electronic screening effect. The contribution of oxygen vacancies is confirmed by the presence of green luminescence (∼2.5 eV) and space-charge-limited current regime from electrical properties measurements. This work is very important for tunable optoelectronic devices based on the doped ZnO system.